2022
DOI: 10.3390/foods11050719
|View full text |Cite
|
Sign up to set email alerts
|

Insight into Bacillus cereus Associated with Infant Foods in Beijing

Abstract: This study was undertaken to investigate the prevalence, antimicrobial resistance, and virulence gene profiles of Bacillus cereus in different brands of infant formula in Beijing supermarkets. Eighty-eight Bacillus cereus isolates were recovered in sixty-eight infant formulas of five domestic brands and fourteen imported brands. The prevalence rate in domestic and imported samples were 70.6% and 52.9%, respectively. Lower mean prevalence level was found in domestic samples (1.17 MPN/g) compared with the import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…The high absorbance, between 200-400 nm, makes it a natural choice for sunscreen and protection treatments, alongside TiO 2 [11][12][13]. As a semiconductor, due to its transparent coccus aureus, Bacillus cereus, Bacillus subtilis, and Enterococcus faecalis, which are responsible for many implants' failure [75,76], skin infections [77], or foodborne illnesses [78], and a fungal strain Candida albicans, responsible for oral and vaginal candidiasis [79][80][81].…”
Section: Introductionmentioning
confidence: 99%
“…The high absorbance, between 200-400 nm, makes it a natural choice for sunscreen and protection treatments, alongside TiO 2 [11][12][13]. As a semiconductor, due to its transparent coccus aureus, Bacillus cereus, Bacillus subtilis, and Enterococcus faecalis, which are responsible for many implants' failure [75,76], skin infections [77], or foodborne illnesses [78], and a fungal strain Candida albicans, responsible for oral and vaginal candidiasis [79][80][81].…”
Section: Introductionmentioning
confidence: 99%
“…On the other extreme, a very low prevalence of the cytK gene was observed (1.1%; 2/181). This is a lower prevalence rate when comparing with other studies on different food products [38,46,52,54,55]. Studies in Europe and around the world have shown that the distribution of the enterotoxin gene cytK is around 40-70% in fresh vegetables [42], quick-frozen food [46], and flour products (including, wheat flour, spelt flour, rye flour, and flour mixes) [56]; however, this prevalence can be higher in other food products including cereals, ready-to-eat meals, spices, dairy products, and starches [57,58].…”
Section: Distribution Of Virulence Genes Among B Cereus Isolatesmentioning
confidence: 55%
“…In China, B . cereus is detected in a variety of foods [ 12 ], like dairy food [ 13 15 ], ready-to-eat products [ 16 ], and meat products [ 17 ]. The actual disease burden is underestimated due to a lack of holistic data on surveillance, posing a food safety risk globally.…”
Section: Introductionmentioning
confidence: 99%
“…In India, 11.4% of readyto-eat food samples were contaminated with B. cereus [9]; in France, B. cereus was recorded as the second or third major cause of foodborne outbreaks between 2006 and 2014 [10]; in Taiwan, it was the uppermost incident bacteria of foodborne diseases [11]. In China, B. cereus is detected in a variety of foods [12], like dairy food [13][14][15], ready-to-eat products [16], and meat products [17]. The actual disease burden is underestimated due to a lack of holistic data on surveillance, posing a food safety risk globally.…”
Section: Introductionmentioning
confidence: 99%